Inert, yet resilient? The National Council for Women's Rights (CNDM) during Bolsonaro’s government (2019-2022) (Simbiótica. Revista Eletrônica, 2025)
According to Bezerra et al. (2024), the National Council for Women’s Rights (CNDM) remained “formally inert” during Bolsonaro’s government (2019–2022). This article challenges that definition by investigating whether and how civil society counselors developed resilient practices during this period. Using Thematic Analysis, the research combines document analysis (minutes from 22 meetings), a bibliographic review on de-democratization and social participation with a gender focus, and semi-structured interviews with three active counselors. The results suggest that, contrary to the aforementioned diagnosis, institutional inertia coexisted with resilience, which became evident in the obstruction of the 5th National Conference on Policies for Women. This action – both cautious and paradoxical – was a strategic effort to protect spaces of dialogue with the State and the public policies that emerge from them
Keywords: democratic backsliding; social participation; feminism; anti-feminism; Nacional Council for Women's Rights (CNDM)